How is using of the Indonesian Banking Environmental Disclosure with GRI? - Amelia, Rizky Windar; Wicaksana, Aditya Pandu; Zulvina, Desi; Sulistyowatie, Syska Lady (Jurnal Penelitian Ekonomi dan Bisnis, 2021)
This study aims to determine how the differences in environmental disclosure in conventional banking with Islamic banking using the GRI index. This study found that conventional banking has a higher environmental disclosure than Islamic banking. In addition, the results of this study state that the disclosure of the Islamic banking environment is more representative when using the ISR index when compared to the GRI index. The data used are in the form of annual reports and sustainability reporting of conventional banking companies and Islamic banking listed on the Indonesia Stock Exchange in 2019. The data analysis technique used in this study is content analysis and statistical tests to confirm the results. Keywords: environmental disclosure, GRI index, ISR index, Indonesian Banking